2020
DOI: 10.1080/14786419.2020.1774759
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibitors from Docynia indica (Wall.) Decne.

Abstract: Nine bioactive compounds, including one new dihydroisocoumarin glycoside, 3Sthunberginol C 6-O-β-D-glucopyranoside (1a/1b), were isolated by chromatographic separation from the fruits of the Vietnamese medicinal plant Docynia indica (Wall.) Decne. 3S-thunberginol C 6-Oβ-D-glucopyranoside was determined as a mixture of boat-like conformers based on NMR evidence and density functional theory (DFT) calculations. The in vitro inhibition of soluble epoxide hydrolase (sEH) by the isolated compounds was comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that thunberginol C has cholinesterase inhibition [ 53 ], soluble epoxide hydrolase inhibition [ 54 ], anti-photoaging effects [ 55 ], antioxidant and anti-microbial [ 56 , 57 ], and cyclooxygenase inhibition (anti-inflammatory) [ 55 ] effects. In this study, it was confirmed that thunberginol C had a protective effect on brain cells and suppressed the expression of anxiety symptoms due to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that thunberginol C has cholinesterase inhibition [ 53 ], soluble epoxide hydrolase inhibition [ 54 ], anti-photoaging effects [ 55 ], antioxidant and anti-microbial [ 56 , 57 ], and cyclooxygenase inhibition (anti-inflammatory) [ 55 ] effects. In this study, it was confirmed that thunberginol C had a protective effect on brain cells and suppressed the expression of anxiety symptoms due to stress.…”
Section: Discussionmentioning
confidence: 99%
“…This could be particularly important in developing countries. Previously, a number of chemicals from a variety of natural sources have been identified as sEHI, including urea- and amide-based inhibitors from plants in the order Brassicales. , However, a large number of these compounds have a low potency or their concentrations in the plant are insufficient for clinical application.…”
mentioning
confidence: 99%